Proposal for One-million-hectare program feasibility study - Nguyan Van Hung (International Rice Research Institute, 2025)
This presentation proposes a pre-feasibility study for Vietnam’s One-million-hectares high-quality, low-emission rice program by consolidating key datasets (e.g., soil–nutrient maps, farmer survey, pilot results, MRV and value-chain data), filling remaining gaps with targeted surveys, then use mapping, modelling and in-depth economic analysis to design what it will take to scale the model. The output is framed as a roadmap and management system for the program, including infrastructure and technology recommendations (AWD water management, residue management, mechanization, logistics, post-harvest), MRV design, value-chain integration, and investment analysis, organized into work packages on infrastructure, capacity/technology development, and management/M&E with multi-stakeholder alignment.